Chemically strengthened lithium aluminosilicate glass with inherent damage resistance
Through the ion exchange technology of Li2O-Al2O3-SiO2-B2O3 glass composition, chemical strengthening is used to use NaNO3 and KNO3 salt baths to solve the shortcomings of lithium aluminosilicate glass in terms of damage resistance and layer depth, and achieve a high indentation threshold. and wear resistance are improved, suitable for consumer electronic products and other applications.
Patent Information
- Application Number
- CN202210786363.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2016-01-08
- Filing Date
- 2017-01-06
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2037-01-06
AI Technical Summary
It is difficult for existing lithium aluminosilicate glass to achieve high damage resistance and deep depth during ion exchange, and traditional glasses have shortcomings in high indentation thresholds and wear resistance.
The Li2O-Al2O3-SiO2-B2O3 glass composition is used for ion exchange, and chemical strengthening is used for salt baths such as NaNO3 and KNO3 to form deep depth and high compression stress, which improves the damage resistance of the glass.
The high damage resistance of lithium aluminum silicate glass is achieved, the indentation fracture toughness is increased to the range of 10kgf to 50kgf, and the Vickers crack-induced threshold and the Nuts scratch threshold are significantly improved, which is suitable for consumer electronic products and other applications.
Smart Images

Figure CN114956551B_ABST
Abstract
Description
[0001] This invention patent application is a divisional application of the invention patent application with international application number PCT / US2017 / 012459, international application date January 6, 2017, application number 201780006069.7 entering the Chinese national phase, and invention name "Chemically strengthened lithium aluminum silicate glass with inherent damage resistance".
[0002] CROSS-REFERENCE TO RELATED APPLICATIONS
[0003] This application claims the benefit of priority under 35 U.S.C. §119 to U.S. Provisional Application Serial No. 62 / 276,431, filed on January 8, 2016, the contents of which are based on this application and are incorporated herein by reference in their entirety. Background Art
[0004] The present disclosure relates to ion-exchangeable glasses. More specifically, the present disclosure relates to ion-exchangeable lithium aluminosilicate glasses. Even more specifically, the present disclosure relates to lithium aluminosilicate glasses that have a high level of inherent damage resistance when ion-exchanged.
[0005] There has been a continuous effort to develop new glass compositions to improve ion exchange characteristics and have higher damage resistance, while facilitating the melting and forming processes. Many glasses with high stress thresholds are based on SiO 2 -Al 2 O 3 -B 2 O 3 -MgO-Na 2 OP 2 O 5 Glass systems. The open structure (ie, high molar volume) due to the presence of boron or phosphorus results in a high intrinsic damage resistance (IDR). Summary of the invention
[0006] Provided by Li 2 O-Al 2 O 3 -SiO 2 -B 2 O 3 A group of glass compositions in the category. These glasses can be 3 and KNO 3The glass is chemically strengthened for a short time (2-4 hours) in a single or multiple ion exchange baths of at least one of the above to form a deep depth of layer (DOL). In some cases, the DOL is at least 70 μm; in other cases, the DOL is at least about 100 μm. The ion-exchanged glass has a high damage resistance (indentation fracture toughness in the range of greater than 10 kgf to greater than 50 kgf), which is better than or at least comparable to that of sodium aluminosilicate glass.
[0007] Therefore, one aspect of the present disclosure provides a lithium aluminosilicate glass. The glass comprises: about 55 mol % to about 75 mol % SiO 2 ; about 9 mol % to about 18 mol % Al 2 O 3 ; about 2.5 mol % to about 20 mol % B 2 O 3 ; about 3 mol % to about 20 mol % Li 2 O; and 0 mol % to about 4 mol % P 2 O 5 .
[0008] Another aspect of the present disclosure provides a lithium aluminosilicate glass. The glass is ion exchanged and has a compressive layer extending from at least one surface into the glass to a layer depth of at least about 70 μm. The compressive layer has a maximum compressive stress of at least about 600 MPa at the surface. The glass also has a Vickers crack initiation threshold of at least about 10 kgf and a Knoop scratch threshold of at least about 8N.
[0009] According to the first aspect of the present disclosure, a lithium aluminosilicate glass is provided. The lithium aluminosilicate glass comprises: about 55 mol % to about 75 mol % of SiO 2 ; about 10 mol % to about 18 mol % Al 2 O 3 ; about 3.5 mol % to about 9.5 mol % B 2 O 3 ; about 7 mol % to about 14 mol % Li 2 O; and 0 mol % to about 4 mol % P 2 O 5 , among which Li 2 O (mol%) / R 2 O (mol %) is in the range of about 0.1 to about 0.4, and R 2 O=Li 2 O+Na 2 O+K 2 O+R 2 O+Cs 2 O.
[0010] According to a second aspect of the present disclosure, the lithium aluminosilicate glass as described in the first aspect is ion-exchanged.
[0011] According to a third aspect of the present disclosure, the ion-exchanged lithium aluminosilicate glass of aspect 2 has a compressive layer extending from at least one surface into the glass to a layer depth of at least about 70 μm, the compressive layer having a maximum compressive stress of at least about 600 MPa.
[0012] According to a fourth aspect of the present disclosure, in the ion-exchanged lithium aluminosilicate glass according to the third aspect, the compressive layer has a compressive stress of at least about 100 MPa at a depth of 50 μm below the surface.
[0013] According to a fifth aspect of the present disclosure, the ion-exchanged lithium aluminosilicate glass according to any one of aspects 2 to 4 has a Vickers crack initiation threshold of at least about 10 kgf.
[0014] According to a sixth aspect of the present disclosure, the ion-exchanged lithium aluminosilicate glass according to any one of aspects 2 to 5 has a Knoop scratch threshold of at least about 8N.
[0015] According to a seventh aspect of the present disclosure, the lithium aluminosilicate glass according to any one of aspects 1 to 6 has a liquidus viscosity of at least about 10 kP.
[0016] According to an 8th aspect of the present disclosure, the softening point of the lithium aluminosilicate glass as described in any one of aspects 1 to 7 is about 840° C. or lower.
[0017] According to a 9th aspect of the present disclosure, the lithium aluminosilicate glass according to any one of aspects 1 to 8 has an annealing point of at least about 510°C.
[0018] According to a tenth aspect of the present disclosure, the elastic modulus of the lithium aluminosilicate glass according to any one of aspects 1 to 9 is at least about 68 GPa.
[0019] According to the 11th aspect of the present disclosure, there is provided the lithium aluminosilicate glass as described in any one of aspects 1 to 10, wherein R 2 O (mol%)–Al 2 O 3 (mol %) is in the range of about -2 mol % to about 5.6 mol %.
[0020] According to the 12th aspect of the present disclosure, there is provided the lithium aluminosilicate glass as described in any one of aspects 1 to 11, wherein Al 2 O 3 (mol%)>B2 O 3 (mol %).
[0021] According to a 13th aspect of the present disclosure, there is provided a lithium aluminosilicate glass as described in any one of aspects 1 to 12, wherein the lithium aluminosilicate glass comprises: about 58 mol % to about 69 mol % of SiO 2 ; about 10 mol % to about 17 mol % Al 2 O 3 ; about 3.5 mol % to about 9.5 mol % B 2 O 3 ; 0 mol % to about 2.5 mol % P 2 O 5 ; about 7 mol % to about 14 mol % Li 2 O; about 0.2 mol % to about 14 mol % Na 2 O; 0 mol % to about 2.5 mol % K 2 O; 0 mol % to about 5 mol % MgO; and 0 mol % to about 4 mol % ZnO, wherein Li 2 O (mol%) / R 2 O (mol %) is in the range of about 0.1 to about 0.4.
[0022] According to a 14th aspect of the present disclosure, there is provided a lithium aluminosilicate glass as described in any one of aspects 1 to 13, wherein the lithium aluminosilicate glass comprises: about 5 mol % to about 9 mol % of B 2 O 3 ; about 7 mol % to about 10 mol % Li 2 O; about 4 mol % to about 14 mol % Na 2 O; and 0 mol % to about 1 mol % K 2 O.
[0023] According to the 15th aspect of the present disclosure, there is provided the lithium aluminosilicate glass as described in any one of aspects 1 to 14, wherein (Al 2 O 3 (mol%) + B 2 O 3 (mol%)) / R 2 O (mol %) is in the range of about 0.9 to about 1.9.
[0024] According to the 16th aspect of the present disclosure, there is provided the lithium aluminosilicate glass as described in any one of aspects 1 to 15, wherein R 2 O (mol%) + R'O (mol%) – Al 2 O 3 (mol%)-B 2 O3 (mol%)-P 2 O 5 (mol %) is in the range of about -10.5 mol % to about -0.11 mol %, where R'O = MgO + CaO + SrO + BaO.
[0025] According to a 17th aspect of the present disclosure, there is provided a lithium aluminosilicate glass as described in any one of aspects 1 to 16, wherein the lithium aluminosilicate glass comprises about 5 mol % to about 12 mol % of Li 2 O.
[0026] According to an 18th aspect of the present disclosure, there is provided a lithium aluminosilicate glass as described in any one of aspects 1 to 17, wherein the lithium aluminosilicate glass comprises: 0 mol % to about 5 mol % of Na 2 O; 0 mol % to about 4 mol % K 2 O; 0 mol % to about 8 mol % MgO; 0 mol % to about 4 mol % ZnO; 0 mol % to about 5 mol % TiO 2 ; and 0 mol % to about 3 mol % of P 2 O 5 .
[0027] According to a 19th aspect of the present disclosure, there is provided a lithium aluminosilicate glass as described in any one of aspects 1 to 18, wherein the lithium aluminosilicate glass comprises: about 55 mol % to about 60 mol % of SiO 2 ; about 12 mol % to about 15 mol % Al 2 O 3 ; about 3.5 mol % to about 7.5 mol % B 2 O 3 ; about 7 mol % to about 10 mol % Li 2 O; and 0 mol % to about 3 mol % P 2 O 5 .
[0028] According to the 20th aspect of the present disclosure, there is provided the lithium aluminosilicate glass as described in any one of aspects 1 to 19, wherein the lithium aluminosilicate glass comprises about 5 mol % to about 7 mol % of B 2 O 3 .
[0029] According to the 21st aspect of the present disclosure, there is provided the lithium aluminosilicate glass as described in any one of aspects 1 to 20, wherein the lithium aluminosilicate glass comprises: 0 mol % to about 5 mol % of Na 2 O; and from about 0.05 mol % to about 0.5 mol % SnO 2 .
[0030] According to the 22nd aspect of the present disclosure, a consumer electronic product is provided. The consumer electronic product comprises: a housing having a front surface, a rear surface and a side surface; an electronic component at least partially located in the housing, the electronic component at least comprising a controller, a memory and a display, the display being located at or adjacent to the front surface of the housing; and a cover glass disposed above the display, wherein at least one of a portion of the housing or the cover glass comprises the lithium aluminum silicate glass as described in any one of aspects 1 to 21.
[0031] According to the 23rd aspect of the present disclosure, a consumer electronic product is provided. The lithium aluminosilicate glass comprises: about 55 mol % to about 75 mol % of SiO 2 ; about 10 mol % to about 18 mol % Al 2 O 3 ; about 2.5 mol % to about 7.5 mol % B 2 O 3 ; about 5 mol % to about 14 mol % Li 2 O; 0 mol % to about 4 mol % P 2 O 5 ; and 0 mol % to about 1 mol % K 2 O; among them, Li 2 O (mol%) / R 2 O (mol%) is in the range of about 0.1 to about 0.4, R 2 O=Li 2 O+Na 2 O+K 2 O+R 2 O+Cs 2 O, R 2 O (mol%) + R'O (mol%) – Al 2 O 3 (mol%)-B 2 O 3 (mol%)-P 2 O 5 (mol %) is in the range of about -10.5 mol % to about -0.11 mol %, and R'O=MgO+CaO+SrO+BaO.
[0032] According to the 24th aspect of the present disclosure, the lithium aluminosilicate glass as described in the 23rd aspect is ion-exchanged.
[0033] According to the 25th aspect of the present disclosure, the ion-exchanged lithium aluminosilicate glass as described in the 24th aspect has a compressive layer, which extends from at least one surface into the glass to a layer depth of at least about 70 μm, and the compressive layer has a maximum compressive stress of at least about 600 MPa.
[0034] According to a 26th aspect of the present disclosure, in the ion-exchanged lithium aluminosilicate glass according to the 25th aspect, the compressive layer has a compressive stress of at least about 100 MPa at a depth of 50 μm below the surface.
[0035] According to a 27th aspect of the present disclosure, the lithium aluminosilicate glass according to any one of aspects 23 to 26 has a Vickers crack initiation threshold of at least about 10 kgf.
[0036] According to a 28th aspect of the present disclosure, the lithium aluminosilicate glass according to any one of aspects 23 to 27 has a Knoop scratch threshold of at least about 8N.
[0037] According to a 29th aspect of the present disclosure, the lithium aluminosilicate glass as described in any one of aspects 23 to 28 has a liquidus viscosity of at least about 10 kP.
[0038] According to a 30th aspect of the present disclosure, the lithium aluminosilicate glass as described in any one of aspects 23 to 29 has a softening point of about 840° C. or less.
[0039] According to a 31st aspect of the present disclosure, the lithium aluminosilicate glass as described in any one of aspects 23 to 30 has an annealing point of at least about 510°C.
[0040] According to a 32nd aspect of the present disclosure, the elastic modulus of the lithium aluminosilicate glass as described in any one of aspects 23 to 31 is at least about 68 GPa.
[0041] According to the 33rd aspect of the present disclosure, there is provided the lithium aluminosilicate glass as described in any one of aspects 23 to 32, wherein R 2 O (mol%)–Al 2 O 3 (mol %) is in the range of about -2 mol % to about 5.6 mol %.
[0042] According to the 34th aspect of the present disclosure, there is provided the lithium aluminosilicate glass as described in any one of aspects 23 to 33, wherein Al 2 O 3 (mol%)>B 2 O 3 (mol %).
[0043] According to the 35th aspect of the present disclosure, there is provided the lithium aluminosilicate glass as described in any one of aspects 23 to 34, wherein (Al 2 O 3 (mol%) + B 2 O 3 (mol%)) / R 2 O (mol %) is in the range of about 0.9 to about 1.9.
[0044] According to a 36th aspect of the present disclosure, there is provided a lithium aluminosilicate glass as described in any one of aspects 23 to 35, wherein the lithium aluminosilicate glass comprises: 0 mol % to about 5 mol % of Na 2 O; 0 mol % to about 8 mol % MgO; 0 mol % to about 4 mol % ZnO; 0 mol % to about 5 mol % TiO 2 ; and 0 mol % to about 3 mol % P 2 O 5 .
[0045] According to a 37th aspect of the present disclosure, there is provided a lithium aluminosilicate glass as described in any one of aspects 23 to 36, wherein the lithium aluminosilicate glass comprises about 5 mol % to about 7 mol % of B 2 O 3 .
[0046] According to the 38th aspect of the present disclosure, there is provided the lithium aluminosilicate glass as described in any one of aspects 23 to 37, wherein the lithium aluminosilicate glass comprises: 0 mol % to about 5 mol % of Na 2 O; and from about 0.05 mol % to about 0.5 mol % SnO 2 .
[0047] According to the 39th aspect of the present disclosure, a consumer electronic product is provided. The consumer electronic product comprises: a housing having a front surface, a rear surface and a side surface; an electronic component at least partially located in the housing, the electronic component at least comprising a controller, a memory and a display, the display being located at or adjacent to the front surface of the housing; and a cover glass disposed above the display, wherein at least one of a portion of the housing or the cover glass comprises the lithium aluminosilicate glass as described in any one of aspects 23 to 38.
[0048] According to the 40th aspect of the present disclosure, there is provided a lithium aluminosilicate glass, wherein the lithium aluminosilicate glass is ion exchanged and has a compressive layer extending from at least one surface into the glass to a layer depth of at least about 70 μm, the compressive layer having a maximum compressive stress of at least about 600 MPa, wherein the glass has a Vickers crack initiation threshold of at least about 10 kgf and a Knoop scratch threshold of at least about 8N.
[0049] According to the 41st aspect of the present disclosure, a consumer electronic product is provided. The consumer electronic product comprises: a housing having a front surface, a rear surface and a side surface; an electronic component at least partially located in the housing, the electronic component at least comprising a controller, a memory and a display, the display being located at the front surface of the housing or adjacent to the front surface of the housing; and a cover glass disposed above the display, wherein at least one of a portion of the housing or the cover glass comprises the lithium aluminum silicate glass as described in the 40th aspect.
[0050] These aspects, advantages, and salient features of the present disclosure and other aspects, advantages, and salient features will be apparent from the following detailed description, the drawings, and the appended claims. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] Figure 1 is a schematic cross-sectional view of a glass product that has undergone ion exchange;
[0052] Figure 2 is the Na from the glass surface to the inside of the glass of the lithium aluminosilicate glass (A) and the glass ceramic (B) disclosed in the present invention. + Concentration distribution diagram;
[0053] Figure 3 The lithium aluminosilicate glass disclosed herein is heated at 390°C in NaNO 3 ion exchange for 3.5 h, and sodium aluminosilicate glass in KNO 3 Figure 1 shows the indentation fracture threshold after ion exchange.
[0054] Figure 4 It is shown that under the pressure head load of 10kgf, 30kgf and 50kgf, Figure 3 Optical micrograph of Vickers indentation in ion-exchanged lithium aluminosilicate glass;
[0055] Figure 5A is a plan view of an exemplary electronic device incorporating any of the articles disclosed herein; and
[0056] Figure 5B yes Figure 5A A perspective view of an exemplary electronic device. DETAILED DESCRIPTION
[0057] In the following description, in several views shown in the accompanying drawings, the same reference numerals represent the same or corresponding parts. It should also be understood that, unless otherwise stated, terms such as "top", "bottom", "outward", "inward", etc. are terms for convenience and should not be regarded as restrictive terms. In addition, whenever a group is described as comprising at least one of a group of elements and their combinations, it should be understood that the group can contain any number of these listed elements in the form of a single element or in combination with each other, or mainly consist of any number of these listed elements, or consist of any number of these listed elements. Similarly, whenever a group is described as consisting of at least one element in a group of elements or their combinations, it should be understood that the group can consist of any number of these listed elements in the form of a single element or in combination with each other. Unless otherwise stated, the numerical range listed includes both the upper and lower limits of the range, as well as any range between the upper and lower limits. Unless otherwise stated, the modifiers "a", "an" and their corresponding modifiers "the" used herein mean "at least one" or "one or more". It should also be understood that the various features disclosed in the specification and drawings can be used in any and all combinations.
[0058] As used herein, the terms "glass article" and "glass articles" are used in their broadest sense to include any object made in whole or in part of glass. Unless otherwise indicated, all compositions are expressed in mole percent (mol %). The unit of coefficient of thermal expansion (CTE) is 10 -7 / °C, and unless otherwise specified, they represent measured values within a temperature range of about 20°C to about 300°C.
[0059] Unless otherwise indicated, all temperatures are expressed in degrees Celsius (°C). As used herein, the term "softening point" refers to the point at which the viscosity of a glass is about 10 7.6 The term "annealing point" refers to the temperature at which the viscosity of the glass is about 10 13.2 The term "200 poise temperature (T 200P )" refers to the temperature at which the viscosity of the glass is about 200 poise. The term "10 11 The "Poise temperature" refers to the viscosity of the glass at about 10 11 The temperature at 35 kP (T 35kP )” refers to the temperature at which the viscosity of the glass is about 35 kilopoise (kP), and the term “160 kP temperature (T 160kP )" refers to the temperature at which the viscosity of the glass is about 160 kP. As used herein, the term "liquidus temperature" or "T L” refers to the temperature at which crystals first appear as molten glass cools from its melting temperature, or the temperature at which the last bit of crystals melts away as the temperature rises from room temperature.
[0060] It should be noted that the terms "substantially" and "about" may be used herein to represent the inherent degree of uncertainty that may be caused by any quantitative comparison, value, measurement, or other representation. These terms are also used herein to represent that a quantitative expression may deviate from a stated reference value without resulting in a change in the basic function of the object to be addressed. Therefore, a glass that is "substantially free of MgO" refers to a glass to which MgO is not actively added or formulated, but may be present in very small amounts (e.g., less than 0.1 mol%) as a contaminant.
[0061] See the accompanying drawings in general and the Figure 1 It should be understood that the examples are for describing specific embodiments of the present disclosure and are not intended to limit the present disclosure or the appended claims. For the sake of clarity and conciseness, the drawings are not necessarily drawn to scale, and certain features and certain views of the drawings may be shown in a scaled-up or schematic manner.
[0062] Ion-exchangeable lithium aluminosilicate glasses are described herein that, when chemically strengthened, exhibit high levels of damage resistance, also referred to as native damage resistance or intrinsic damage resistance, as characterized by Vickers crack initiation threshold and Knoop scratch tests. These glasses are 3 ) are generally more likely to exchange ions in sodium alkali aluminosilicate glasses than in potassium salts such as KNO 3 ) at a faster rate. Deeper compression depths (also called “depth of layer” or “DOL”) can also be achieved at lower temperatures using lithium-containing glasses. When Na+ replaces Li+ in the glass, the diffusion rate can be faster than that of K+. + Exchange Na in glass + About 10 times faster. A mixed salt bath can be used to perform a double ion exchange, in which both K + Exchange Na + Na occurs again + Exchange Li + , thus due to Na + Exchange Li + The deep compression depth and the K + Exchange Na + This results in high surface compressive stress.
[0063] The lithium aluminosilicate glass described herein comprises or consists essentially of about 55 mol % to about 75 mol % SiO 2 (55 mol %≤SiO 2≤75 mol %); about 9 mol % to about 18 mol % Al 2 O 3 (9 mol %≤Al 2 O 3 ≤18 mol %); about 2.5 mol % to about 20 mol % B 2 O 3 (2.5 mol % ≤ B 2 O 3 ≤20 mol %); about 3 mol % to about 20 mol % Li 2 O(3 mol %≤Li 2 O≤20 mol %); 0 mol % to about 4 mol % P 2 O 5 (0 mol % ≤ P 2 O 5 ≤4 mol %). In some embodiments, the glass further comprises at least one of: 0 mol % to about 5 mol % of Na 2 O; 0 mol % to about 4 mol % K 2 O; 0 mol % to about 8 mol % MgO; 0 mol % to about 4 mol % ZnO and 0 mol % to about 5 mol % TiO 2 .
[0064] In specific embodiments, the lithium aluminosilicate glass described herein comprises or consists essentially of about 55 mol % to about 75 mol % SiO 2 ; about 10 mol % to about 18 mol % Al 2 O 3 ; 0 mol % to about 20 mol % B 2 O 3 ; about 5 mol % to about 14 mol % Li 2 O; 0 mol % to about 5 mol % Na 2 O; 0 mol % to about 4 mol % K 2 O; 0 mol % to about 8 mol % MgO; 0 mol % to about 4 mol % ZnO; 0 mol % to about 5 mol % TiO 2 ; 0 mol % to about 4 mol % P 2 O 5 and about 0.05 mol % to about 0.5 mol % SnO 2 Even more specifically, the glass may include or consist essentially of about 55 mol % to about 60 mol % SiO 2 (55 mol %≤SiO 2 ≤60 mol %); about 12 mol % to about 15 mol % Al 2 O 3 (12 mol %≤Al2 O 3 ≤15 mol %); about 2.5 mol % to about 7.5 mol % of B 2 O 3 (2.5 mol % ≤ B 2 O 3 ≤7.5 mol %); about 7 mol % to about 10 mol % Li 2 O(7 mol %≤Li 2 O≤10 mol %); and 0 mol % to about 3 mol % of P 2 O 5 (0 mol % ≤ P 2 O 5 ≤3 mol %). Most preferably, B 2 O 3 In the range of about 5 mol% to about 7 mol%. Non-limiting examples of the composition of the glass and a reference composition (9667) are listed in Table 1.
[0065] Table 1. Examples of lithium aluminosilicate glasses
[0066]
[0067]
[0068]
[0069] In specific embodiments, the lithium aluminosilicate glass described herein comprises or consists essentially of about 58 mol % to about 69 mol % SiO 2 (58 mol %≤SiO 2 ≤69 mol %); about 9 mol % to about 17 mol % Al 2 O 3 (9 mol %≤Al 2 O 3 ≤17 mol %); about 3.5 mol % to about 9.5 mol % of B 2 O 3 (3.5 mol % ≤ B 2 O 3 ≤9.5 mol %); 0 mol % to about 2.5 mol % of P 2 O 5 (0 mol % ≤ P 2 O 5 ≤4 mol %); about 2.5 mol % to about 12 mol % Li 2 O(2.5 mol %≤Li 2 O≤12 mol %); about 0.2 mol % to about 12 mol % Na 2 O(0.2 mol %≤Na 2O≤13 mol %); 0 mol % to about 2.5 mol % K 2 O(0 mol %≤K 2 O≤2.5 mol %); 0 mol % to about 5 mol % of MgO (0 mol %≤MgO≤5 mol %); and / or 0 mol % to about 4 mol % of ZnO (0 mol %≤ZnO≤4 mol %). More specifically, the glass may include: about 5 mol % to about 9 mol % of B 2 O 3 (5 mol % ≤ B 2 O 3 ≤9 mol %); about 4 mol % to about 10 mol % Li 2 O(4 mol %≤Li 2 O≤10 mol %); about 4 mol % to about 14 mol % Na 2 O(4 mol %≤Na 2 O≤14 mol %); 0 mol % to about 1 mol % K 2 O(0 mol %≤K 2 O≤1 mol %); 0 mol % to about 3 mol % MgO (0 mol %≤MgO≤3 mol %); and / or 0 mol % to about 3 mol % ZnO (0 mol %≤ZnO≤3 mol %). These glasses may also include about 0.05 mol % to about 0.5 mol % SnO 2 (0.05 mol %≤SnO 2 ≤0.5 mol %). Non-limiting examples of the composition of the glass are listed in Table 2.
[0070] In some embodiments, (Li 2 O (mol%) / R 2 O (mol%) is in the range of about 0.1 to about 0.5 (0.1≤(Li 2 O (mol%) / R 2 O (mol%) ≤ 0.5), where R 2 O=Li 2 O+Na 2 O+K 2 O+R 2 O+Cs 2 O.
[0071] In some embodiments, R 2 O (mol%)–Al 2 O 3 (mol%) is in the range of about -2 mol% to about 5.6 mol%, wherein R 2 O=Li 2 O+Na 2 O+K 2 O+R 2 O+Cs2 O. In some embodiments, Al 2 O 3 (mol%)>B 2 O 3 (mol%). In some embodiments, (Al 2 O 3 (mol%) + B 2 O 3 (mol%)) / R 2 O (mol%) is in the range of about 0.9 to about 1.9. In some embodiments, R 2 O (mol%) + R'O (mol%) – Al 2 O 3 (mol%)-B 2 O 3 (mol%)-P 2 O 5 (mol %) is in the range of about -10.5 mol % to about -0.11 mol %, where R'O = MgO + CaO + SrO + BaO.
[0072] In some embodiments, the softening point of the lithium aluminosilicate glass described herein is lower than that of the sodium aluminosilicate glass, which generally has a softening point greater than about 900°C. In some embodiments, the softening point of the glass described herein is about 840°C or less. In certain embodiments, the softening point of the glass is about 820°C or less, and in other embodiments, it is about 800°C or less. These low softening points are accompanied by a coefficient of thermal expansion (CTE) that is lower than the CTE of the sodium aluminosilicate glass. The lower CTE is important for maintaining dimensional stability when the glass sheet is reshaped. In addition to use as a flat sheet, the relatively low CTE of the glass disclosed herein enables its use as a three-dimensional article and for automotive applications.
[0073] In some embodiments, the lithium aluminosilicate glasses described herein have an annealing point of at least about 500° C. In certain embodiments, the glasses have an annealing point of at least about 520° C., and in other embodiments, at least about 530° C.
[0074] Table 2 lists the density, strain point, softening point, annealing point and coefficient of thermal expansion (CTE) for selected glass compositions.
[0075] Table 2. Composition, density, strain point, softening point, annealing point and coefficient of thermal expansion (CTE) of selected lithium aluminosilicate glasses.
[0076]
[0077]
[0078]
[0079]
[0080]
[0081]
[0082]
[0083]
[0084]
[0085]
[0086]
[0087]
[0088]
[0089]
[0090]
[0091]
[0092]
[0093]
[0094]
[0095]
[0096]
[0097]
[0098]
[0099]
[0100]
[0101]
[0102]
[0103]
[0104]
[0105]
[0106]
[0107]
[0108]
[0109]
[0110]
[0111]
[0112]
[0113]
[0114] In some embodiments, the lithium aluminosilicate glasses described herein may have an elastic modulus of at least about 68 gigapascals (GPa).
[0115] In addition to exemplary lithium silicate glass compositions, Table 2 lists the physical properties of these exemplary glasses, including strain point, annealing point, and softening point; CTE and density. The strain point was determined using the beam bending viscosity method of ASTM C598-93 (2013). The annealing point was determined using the beam bending viscosity method of ASTM C598-93 (2013). The softening point was determined using the parallel plate viscosity method of ASTM C1351M-96 (2012). The linear coefficient of thermal expansion (CTE) over the temperature range of 0-300°C is expressed in ppm / K and is determined using a push rod dilatometer in accordance with ASTM E228-11. The density was determined using the buoyancy method of ASTM C693-93 (2013).
[0116] In some embodiments, the lithium aluminosilicate glasses described herein have a liquidus viscosity greater than about 10,000 poise (P), and in certain embodiments, greater than 100,000 P. In some embodiments, these glasses are compatible with fusion processes (such as fusion draw processes, etc.) and are compatible with zircon hardware used for forming. However, in some embodiments (such as Example 3 in Table 1), these glasses have a low liquidus viscosity and are therefore not fusion-formable. In these cases, the glass can be formed by slot drawing, float, rolling, and other sheet forming processes known in the art.
[0117] The glasses described herein can be formed into articles, such as, but not limited to, flat sheets and three-dimensional articles, having a thickness ranging from about 0.2 mm up to about 2 mm, and in some embodiments, from about 0.5 mm to about 1.5 mm.
[0118] Viscosity and mechanical properties are affected by the glass composition. In the glass compositions described herein, SiO 2 Serves as the main glass-forming oxide and can be used to stabilize the network structure. SiO 2 The concentration of SiO should be high enough to provide a glass with sufficient chemical durability to be suitable for consumer applications. However, pure SiO 2 Or high SiO 2 The melting temperature of glass with SiO content (200 poise temperature) is too high to process the glass by certain methods. 2 The presence of reduces the compressive stress formed by ion exchange. In certain embodiments, the lithium aluminosilicate glass described herein includes about 55 mol % to about 75 mol % SiO 2 , such as about 57 mol % to about 73 mol % SiO 2 ; about 59 mol % to about 71 mol % SiO 2 ; about 61 mol % to about 69 mol % SiO 2 ; about 63 mol % to about 67 mol % SiO 2 ; about 55 mol % to about 60 mol % SiO 2 ; about 58 mol % to about 69 mol % SiO 2 ; or any subrange contained therein.
[0119] In these glasses, Al 2 O 3 It can also be used as a glass former. Similar to SiO 2 Alumina generally increases the viscosity of the melt, and relative to alkali metal elements or alkaline earth metal elements, Al 2 O 3 The increase in the amount of aluminum ions generally improves durability. The structural effect of aluminum ions depends on the glass composition. When the alkali metal oxide (R 2 O) concentration is close to or greater than that of aluminum oxide (Al 2 O 3 ) concentration, it was found that all the aluminum was tetrahedrally coordinated and the alkali metal ions acted as charge balancers. This was true for all the glasses described in this article. 2 O 3 It also plays an important role in ion-exchangeable glasses because it can provide a strong network framework (i.e., high strain point) while allowing relatively fast diffusion rates of alkali ions. 2 O3 Concentration generally reduces the liquidus viscosity, so it is necessary to 2 O 3 The concentration is controlled within a reasonable range. In some embodiments, the glasses described herein include about 9 mol % to about 18 mol % Al 2 O 3 , such as about 10 mol % to about 18 mol % Al 2 O 3 ; about 12 mol % to about 16 mol % Al 2 O 3 ; about 12 mol % to about 15 mol % Al 2 O 3 ; about 9 mol % to about 17 mol % Al 2 O 3 ; or any subrange contained therein.
[0120] Alkali metal oxides (Li 2 O、Na 2 O.K 2 O、Rb 2 O and Cs 2 O) acts as an acid in achieving low melting temperatures and low liquidus temperatures. On the other hand, the addition of alkali metal oxides sharply increases the coefficient of thermal expansion (CTE) and reduces chemical durability. Most importantly, the presence of at least one small alkali metal oxide (such as Li 2 O and Na 2 O) to exchange with larger alkali metal ions (e.g., K) from an ion exchange medium (e.g., a salt bath). + ) exchange. Generally, three types of ion exchange can be performed: Na + Exchange Li + , which results in a deep layer depth but low compressive stress; K + Exchange Li + , which results in a shallow layer depth but a relatively large compressive stress; and K + Exchange Na + , which results in moderate depth of layer and compressive stress. Since compressive stress is proportional to the amount of alkali metal ions ion-exchanged from the glass, a sufficiently high concentration of at least one small alkali metal oxide is necessary to produce large compressive stress in the glass. In certain embodiments, the glasses described herein include about 2.5 mol % to about 20 mol % Li 2 O, such as about 3 mol % to about 20 mol % Li 2 O; about 4 mol % to about 18 mol % Li 2 O; about 5 mol % to about 16 mol % Li2 O; about 6 mol % to about 14 mol % Li 2 O; about 5 mol % to about 14 mol % Li 2 O; about 7 mol % to about 10 mol % Li 2 O; about 2.5 mol % to about 12 mol % Li 2 O; about 4 mol % to about 10 mol % Li 2 O; or any subranges subsumed therein. In some embodiments, the glasses include 0 mol % to about 14 mol % Na 2 O, such as 0 mol % to about 5 mol % Na 2 O; about 0.2 mol % to about 12 mol % Na 2 O; about 4 mol % to about 14 mol % Na 2 O; 0.2 mol % to about 14 mol % Na 2 O; or any subranges subsumed therein. In some embodiments, the glasses described herein may include 0 mol % to about 4 mol % of K 2 O, such as 0 mol % to about 2.5 mol % K 2 O; 0 mol % to about 1 mol % K 2 O; or any subrange contained therein.
[0121] In order to obtain a high liquidus viscosity and thus to be formed by down-drawing techniques, in particular by fusion drawing, the glass should have a molar content of Li 2 O should account for less than half of the total alkali metal oxide content. 2 O / (Li 2 O+Na 2 O+K 2 O+R 2 O+Cs 2 When the LiO) exceeds 0.5, the spodumene liquidus viscosity increases and the glass is no longer compatible with fusion technology. 2 O / (Li 2 O+Na 2 O+K 2 O+R 2 O+Cs 2 O) is in the range of about 0.1 to about 0.5; for example 0.1≤Li 2 O / (Li 2 O+Na 2 O+K 2 O+R 2 O+Cs 2 O)≤0.4、0.2≤Li 2 O / (Li 2 O+Na2 O+K 2 O+R 2 O+Cs 2 O)≤0.4, or any subrange contained herein. However, in order to obtain high compressive stress after ion exchange, it is desirable to make Li 2 O content is maximized. Therefore, in order to obtain a compressive stress greater than 100 MPa at a depth greater than 40 μm, Li 2 The O content should be greater than about 4 mol %, and in some embodiments, preferably greater than about 5 mol %, and should be less than about 10 mol %.
[0122] K 2 The existence of O makes K + Ion exchange Na + The rate of ion exchange increases, but the compressive stress after ion exchange decreases sharply. In some embodiments, the glass should include less than about 2.5 mol% K 2 O, and in certain embodiments, K 2 The O concentration should not exceed 1 mol %.
[0123] Divalent cation oxides (e.g., alkaline earth metal oxides and ZnO) also improve the solubility of the glass. However, for ion exchange performance, the presence of divalent cations reduces the mobility of alkali metal cations. This negative impact on ion exchange performance becomes significant for larger divalent cations. In addition, smaller divalent cation oxides are generally more conducive to enhancing compressive stress than larger divalent cation oxides. Therefore, MgO provides many advantages in improving stress relaxation while minimizing the adverse effects on alkali metal diffusivity. However, when the content of MgO is high, the glass is prone to forming forsterite (Mg 2 SiO 4 ), which causes a very steep increase in liquidus temperature as the MgO concentration rises above a certain level. In some embodiments, MgO is the only divalent cation oxide present in the glass. In other embodiments, the glasses described herein may include at least one of MgO and ZnO. Thus, in some embodiments, these glasses may include 0 mol % to about 8 mol % MgO, such as 0 mol % to about 6 mol % MgO; 0 mol % to about 5 mol % MgO; 0 mol % to about 3 mol % MgO; 0 mol % to about 1 mol % MgO; or any sub-ranges subsumed therein. In some embodiments, the glass includes 0 mol % to about 4 mol % ZnO, such as 0 mol % to about 3 mol % ZnO; 0 mol % to about 2 mol % ZnO; 0 mol % to about 1 mol % ZnO, or any sub-ranges subsumed therein.
[0124] When boron is not charge balanced by an alkali metal oxide or a divalent cation oxide, it will be in a tri-coordinate state and open up the glass structure. The network around tri-coordinate boron is not as rigid as the network around tetra-coordinate boron; the bonds are "soft (i.e., elastic, flexible, or able to bend or stretch)", thus allowing the glass to withstand some degree of deformation before cracks form. In addition, boron reduces the melt viscosity and effectively helps to suppress the zircon decomposition viscosity of the glass. In some embodiments, the glasses described herein include 0 mol% to about 20 mol% B 2 O 3 , for example, about 2.5 mol % to about 20 mol % B 2 O 3 ; about 3 mol % to about 18 mol % B 2 O 3 ; about 3.5 mol % to about 16 mol % B 2 O 3 ; about 4 mol % to about 16 mol % B 2 O 3 ; about 4.5 mol % to about 14 mol % B 2 O 3 ; about 5 mol % to about 12 mol % B 2 O 3 ; about 2.5 mol % to about 7.5 mol % B 2 O 3 ; about 5 mol % to about 7 mol % B 2 O 3 ; about 3.5 mol % to about 9.5 mol % B 2 O 3 ; about 5 mol % to about 9 mol % B 2 O 3 ; or any subrange contained therein.
[0125] P 2 O 5 Improves damage resistance and does not hinder ion exchange. In some embodiments, phosphorus is added to the glass to form silicon dioxide (SiO 2 ) is aluminum phosphate (AlPO 4 ) substituted structure, which is composed of tetracoordinated aluminum and phosphorus and / or boron phosphate (BPO 4 ), wherein the boron phosphate is composed of tetracoordinated boron and phosphorus. In some embodiments, the glass includes 0 mol % to about 4 mol % of P 2 O 5 , for example 0 mol % to about 3 mol % P 2 O 5 ; 0 mol % to about 2.5 mol % P 2 O 5; 0 mol % to about 1 mol % P 2 O 5 ; or any subrange contained therein.
[0126] If glass ceramic products are required, TiO 2 It acts as a nucleating agent to produce bulk nucleation. 2 If the concentration of is too low, the precursor glass does not crystallize. If the concentration is too high, it is difficult to control crystallization after cooling during the formation of the precursor glass. In some embodiments, the glasses described herein may include 0 mol % to about 5 mol % TiO 2 , for example 0 mol % to about 4 mol % TiO 2 ; 0 mol % to about 3 mol % TiO 2 ; 0 mol % to about 2 mol % TiO 2 ; 0 mol % to about 1 mol % TiO 2 ; or any subrange contained therein.
[0127] In some embodiments, the glasses described herein may further include at least one fining agent, such as but not limited to SnO 2 、As 2 O 3 , Sb 2 O 3 etc. As is not usually included in glass due to environmental and toxicity issues 2 O 3 and Sb 2 O 3 Therefore, the glasses described herein generally do not contain As 2 O 3 and Sb 2 O 3 , and in some embodiments, these glasses may include about 0.05 mol % to about 0.5 mol % SnO 2 .
[0128] Rare earth oxides can increase the hardness and elastic modulus of glass, but they hinder ion exchange, increase the density and cost of glass, and give glass many colors. Therefore, it is desirable to limit the total content of rare earth oxides to less than 0.1 mol%.
[0129] In some aspects, the lithium aluminosilicate glasses described herein are strengthened by forming a compressive layer on the surface of the glass. In certain embodiments, the glasses are chemically strengthened, and in specific embodiments, the glasses are chemically strengthened by ion exchange.
[0130] Ion exchange is the process of exchanging the larger cations present in the ion exchange medium (e.g., molten salt bath or paste) with the smaller cations in the glass. In a specific embodiment, ion exchange is carried out by immersing the glass in a molten bath of a salt substantially containing larger cations. The ion exchange bath may also contain salts of smaller cations present in the glass. As used herein, the term "substantially containing" means that other components may be present in the molten salt bath. These components may include, but are not limited to, compounds for reducing the corrosion of the bath container or glass products by the molten salt. These additional components may include, but are not limited to, selected components of the glass, such as silicic acid, alumina in gel form, silica in gel form, etc.
[0131] Figure 1 A schematic cross-sectional view of a glass article that has undergone ion exchange is shown. The glass article 100 has a thickness t, a first surface 110, and a second surface 112. In some embodiments, the thickness t of the glass article 100 is up to about 1 mm. Figure 1 The illustrated embodiment depicts the glass article 100 as a flat planar sheet or plate, but the glass article may have other configurations, such as a three-dimensional shape or a non-planar configuration. The glass article 100 has a first compressive layer 120 extending from the first surface 110 to a depth of layer (DOL) d into the body of the glass article 100. 1 .exist Figure 1 In the illustrated embodiment, the glass article 100 further comprises a second compressive layer 122 extending from the second surface 112 to a second layer depth d 2 The first and second compressive layers 120, 122 are each under a compressive stress CS. In some embodiments, the first and second compressive layers 120, 122 each have a maximum compressive stress at the first and second surfaces 110, 112, respectively. The glass article also has a central region 130, which is oriented from d 1 Extend to d 2 The central region 130 is under tensile stress or central tension (CT), which balances or counteracts the compressive stresses of the layers 120 and 122. The layer depths d of the first and second compressive layers 120, 122 are 1 d 2 The glass article 100 is protected from the propagation of a defect introduced by a sharp impact to the first and second surfaces 110, 112 of the glass article 100, while the compressive stress of at least about 900 MPa causes the defect to penetrate through the first and second compressive layers 120, 122 to a depth d 1 d 2 The possibility is the smallest.
[0132] When ion exchanged, the lithium aluminosilicate glasses described herein generally exhibit a deeper depth of layer and lower central tension than sodium aluminosilicate glasses, thus enabling chemical strengthening of extremely thin (ie, <0.5 mm) glass sheets while being less susceptible to brittleness.
[0133] Compressive stress (including surface CS) is measured by a surface stress meter (FSM), using a commercially available instrument such as the FSM-6000 manufactured by Orihara Industrial Co., Ltd. (Japan). Surface stress measurement relies on accurate measurement of the stress optical coefficient (SOC), which is related to the birefringence of the glass. SOC is measured in turn according to Protocol C (Glass Disk Method) described in ASTM Standard C770-16, entitled "Standard Test Method for Measurement of Glass Stress-Optical Coefficient," which is incorporated herein by reference in its entirety.
[0134] As used herein, DOL refers to the depth at which stress in a chemically strengthened alkali aluminosilicate glass article described herein changes from compressive stress to tensile stress. Depending on the ion exchange treatment, DOL can be measured by FSM or scattered light polarizer (SCALP). If the stress in the glass article is generated by exchanging potassium ions into the glass article, the DOL is measured using FSM. If the stress in the glass article is generated by exchanging sodium ions into the glass article, the DOL is measured using SCALP. If the stress in the glass article is generated by exchanging both potassium ions and sodium ions into the glass, the DOL is measured using SCALP because it is believed that Na+ is the most important ion exchanger. + The depth of exchange of ions ("potassium DOL") represents the DOL, and the depth of exchange of potassium ions represents the magnitude of the change in compressive stress (but does not represent a change in stress from compression to tension). The penetration depth of K+ ions ("potassium DOL") represents the depth of potassium penetration caused by the ion exchange process. The potassium DOL of the articles described herein is generally less than the DOL. The potassium DOL is measured using a surface stress gauge, such as a commercially available FSM-6000 surface stress gauge manufactured by Luceo Co., Ltd., Tokyo, Japan. As described above for CS measurements, the measurement of potassium DOL relies on the accurate measurement of the stress optical coefficient (SOC).
[0135] The lithium aluminosilicate glass described herein can be subjected to an ion exchange process in at least one molten salt bath containing either a sodium salt, a potassium salt, or both a sodium salt and a potassium salt. Nitrate NaNO is typically used in the ion exchange process. 3 and KNO 3 The glass is maintained in the salt bath for a time sufficient to allow ion exchange to occur on the surface and to a certain depth in the article. In one embodiment, the glass is immersed in a bath containing NaNO 3 Chemical strengthening is performed by placing the glass in a molten salt for a predetermined period of time to achieve the desired ion exchange level. + Ions are Na + or K + ion replacement, and Na + Ions and K + The ionic radius of the ions is larger than that of Li + ion radius, thereby forming a surface compression layer. In one embodiment, the temperature of the molten salt bath is about 390°C, and the predetermined time is in the range of about 1 to 4 hours. In other embodiments, the ion exchange is performed in at least one molten salt bath at a temperature of about 370°C to about 390°C.
[0136] In some embodiments, the glasses described herein can undergo ion exchange with monovalent silver cations to provide glass surfaces with antimicrobial properties. + The ionic radius is larger than Li + Or Na + The ionic radius of either species is smaller than that of the other, so silver ion exchange of these glasses results in a lower loss of compressive stress than that observed in ion-exchanged glasses containing only sodium and potassium.
[0137] In some embodiments, the lithium aluminosilicate glasses described herein can be ion exchanged to obtain a depth of layer of at least about 70 μm when the ion exchange time is less than about 7 hours. In addition, these glasses can be ion exchanged to obtain a maximum compressive stress of at least about 500 MPa at the glass surface in a one-step ion exchange process, or at least about 600 MPa at the glass surface in a two-step ion exchange process, wherein some glasses obtain a maximum compressive stress of up to 840 MPa in a one-step ion exchange process, and a maximum compressive stress of up to 1000 MPa at the glass surface in a two-step ion exchange process. In some embodiments, a compressive stress of at least about 700 MPa, or at least about 800 MPa, or at least about 900 MPa can be obtained using either a one-step ion exchange process or a two-step ion exchange process. In some embodiments, the compressive stress at a depth of 100 μm or more below the surface in these ion exchanged glasses can be about 50 MPa or more.
[0138] The lithium aluminosilicate glasses described herein can be ion exchanged to obtain a compressive layer depth of at least about 70 μm, in one embodiment, at least about 100 μm, and in other embodiments, at least about 150 μm, by either a one-step ion exchange process or a two-step ion exchange process. The ion exchange time required to obtain these layer depths by either a one-step ion exchange process or a two-step ion exchange process is less than about 7 hours at a temperature of 370° C. to about 390° C.
[0139] The compression layer distribution and depth can be determined by the concentration distribution of the larger cations participating in the ion exchange process. Figure 2 The Na content from the glass surface to the inner part of 1) lithium aluminosilicate glass (Example 3 in Table 1) and glass ceramic cerammed at 975°C for 4 hours (Corning No. 9667; nominal composition is listed in Table 1) is shown. + Concentration distribution of the two substances at 390℃ in NaNO 3 In some embodiments, the lithium aluminosilicate glass can obtain a layer depth DOL (DOL) of at least 100 μm. Figure 2 1) in the above, through Na 2 O concentration distribution.
[0140] Table 3 lists the conditions, CS, K of the one-step ion exchange for the composition selected from Table 2. + The penetration depth into the glass and the Na + Table 4 lists the two-step ion exchange conditions, fictive temperature T for the composition selected from Table 2. f , CS and DOL.
[0141] Table 3. One-step ion exchange conditions, compressive stress (CS) and K for compositions selected from Table 2 + and Na + penetration.
[0142]
[0143]
[0144]
[0145]
[0146] Table 4. Two-step ion exchange conditions and fictive temperature T for the composition selected from Table 2 f , CS and DOL.
[0147]
[0148] The Vickers crack initiation threshold described herein is determined by applying an indentation load to the glass surface and then removing the indentation load at a rate of 0.2 mm / minute. The maximum indentation load is maintained for 10 seconds. The indentation crack threshold is defined as the indentation load at which 50% of 10 indentations exhibit any number of radial / intermediate cracks extending from the corners of the indentation mark under the indentation load. The maximum load is increased until the threshold of a given glass composition is reached. All indentation measurements are carried out at room temperature and 50% relative humidity. The test involves the use of a square-based diamond cone indenter with an angle of 136° between the faces, which is referred to as a Vickers indenter. The Vickers indenter is identical to the indenter used in the standard microhardness test (reference ASTM-E384-11).
[0149] As used herein, the term "Knoop scratch threshold" refers to the occurrence of transverse cracking. In the Knoop threshold test, a mechanical tester scratches the glass using a Knoop diamond with increasing loads to determine the occurrence of transverse cracking. As used herein, the Knoop scratch threshold is the occurrence of transverse cracking (3 or more times out of 5 indentation events). In the Knoop scratch transverse cracking threshold test, the glass article and samples of each article are first scratched using a Knoop indenter under dynamic load or increasing load to determine the load range for the occurrence of transverse cracking for the sample population. Once the load range that can be applied is determined, a series of increasing constant load scratches (3 minutes or more at each load) are performed to determine the Knoop scratch threshold. The Knoop scratch threshold range is determined by comparing test specimens with one of three failure modes: 1) a sustained transverse surface crack greater than twice the groove width, 2) damage contained within the groove, but with the presence of a transverse surface crack less than twice the groove width and damage visible to the naked eye, or 3) the presence of a large subsurface transverse crack greater than twice the groove width and / or the presence of an intermediate crack at the scratch apex.
[0150] When NaNO 3 When ion exchange is performed in the presence of a catalyst, the glasses described herein exhibit high native damage resistance, and in some embodiments, the glasses described herein can achieve a Vickers crack initiation threshold exceeding 50 kilograms of force (kgf). 2 O glass at 390 °C in NaNO 3 This level of damage resistance can be achieved after 3.5 hours of ion exchange in the bath.This Vickers crack initiation threshold is comparable to or greater than that exhibited by similar sodium aluminosilicate glasses that have high levels of intrinsic damage resistance. Figure 3 The following substances are in KNO 3 Figure 2 shows the indentation fracture threshold (IFT) diagram determined after ion exchange in the lithium aluminosilicate glass of the present disclosure (Example 3 in Table 1, at 390°C in NaNO 3 Ion exchange for 3.5 hours)( Figure 3 C), and fusion-formed sodium aluminosilicate glasses A and E (nominal composition: 67.6 mol % SiO 2 ; 3.7 mol% B 2 O 3 ; 12.7 mol% Al 2 O 3 ; 13.7 mol% Na 2 O; 0.01 mol% K 2 O; 2.3 mol% MgO and 0.1 mol% SnO 2), where IFT is 15-20 kgf; Glass B (nominal composition: 64.7 mol% SiO 2 ; 5.1 mol% B 2 O 3 ; 13.9 mol% Al 2 O 3 ; 13.7 mol% Na 2 O; 2.4 mol% MgO and 0.08 mol% SnO 2 ), wherein the IFT is 30-40 kgf; and glass D (nominal composition: 64.7 mol % SiO 2 ; 5.1 mol% B 2 O 3 ; 13.9 mol% Al 2 O 3 ; 13.7 mol% Na 2 O; 2.4 mol% MgO and 0.08 mol% SnO 2 ), where IFT is 15kgf. Figure 4 It is shown that at 10kgf ( Figure 4 Under the pressure head loads of (a), 30kgf (b) and 50kgf (c), Figure 3 Optical micrograph of a Vickers indentation in an ion-exchanged lithium aluminosilicate glass. Figure 4 The image in shows significant glass densification without the formation of transverse cracks, indicating that the glass has a high level of inherent damage resistance.
[0151] In some embodiments, when ion exchanged as detailed above, the glasses described herein may exhibit a Vickers crack initiation threshold (VIT) of at least 10 kgf; in some embodiments, at least 15 kgf; in other embodiments, at least about 20 kgf. In certain embodiments, the Vickers crack initiation threshold is in the range of about 10 kgf to about 35 kgf, and the Knoop scratch threshold (KST) is in the range of about 10 Newtons (N) to about 20N.
[0152] Tables 3 and 4 list the Vickers crack initiation threshold (VIT) and Knoop scratch threshold (KST) of glasses ion exchanged in a one-step ion exchange process and a two-step ion exchange process, respectively.
[0153] The articles disclosed herein can be incorporated into another article, such as an article having a display (or display article) (e.g., consumer electronic devices, including mobile phones, tablets, computers, navigation systems, etc.); architectural articles; transportation articles (e.g., automobiles, trains, aircraft, ships, etc.), appliance articles, or any article requiring a certain degree of transparency, scratch resistance, abrasion resistance, or a combination of the above properties. Figure 5Aand 5B Exemplary articles comprising any of the reinforced articles disclosed herein are shown. Specifically, Figure 5A and 5B A consumer electronic device 200 is shown, which includes a housing 202 having a front surface 204, a rear surface 206, and side surfaces 208; electronic components (not shown) at least partially or completely located within the housing and including at least a controller, a memory, and a display 210 at or adjacent to the front surface of the housing; and a cover substrate 212 at or above the front surface of the housing such that the cover substrate 212 is above the display. In some embodiments, the cover substrate 212 and / or the housing can include any of the reinforced articles disclosed herein.
[0154] Although typical embodiments are given for illustration, the foregoing description should not be considered as limiting the scope of the present disclosure or the appended claims. Therefore, those skilled in the art may think of various improvements, modifications and alternative forms without departing from the spirit and scope of the present disclosure and the appended claims.
Claims
1. A lithium aluminosilicate glass comprising: 55 mol% to 75 mol% SiO2; 10 mol % to 18 mol % Al2O3; 3.5 mol % to 9.5 mol % B2O3; 7 mol % to 10 mol % Li2O; and 0 mol% to 4 mol% P2O5, Among them, Li2O (mol %) / R2O (mol %) is in the range of 0.20 to 0.4, and R2O = Li2O + Na2O + K2O + Rb2O + Cs2O, and the sum of all components of the glass is 100 mol %.
2. A lithium aluminosilicate glass comprising: 55 mol % to 75 mol % SiO2; 10 mol % to 18 mol % Al2O3; 2.5 mol % to 7.5 mol % B2O3; 5 mol % to 12 mol % Li2O; 0 mol % to 4 mol % P2O5; and 0 mol % to 1 mol % K2O, Among them, Li2O (mol %) / R2O (mol %) is in the range of 0.322 to 0.4, R2O = Li2O + Na2O + K2O +Rb2O + Cs2O, R2O (mol %) + R'O (mol %) - Al2O3 (mol %) - B2O3 (mol %) - P2O5 (mol %) is in the range of -10.5 mol % to -0.11 mol %, and R'O = MgO + CaO + SrO + BaO, and the sum of all components of the glass is 100 mol %.
3. A lithium aluminosilicate glass comprising: 59.979 mol % to 75 mol % SiO2; 10 mol % to 17 mol % Al2O3; 2.4 mol % to 7.5 mol % B2O3; 5.969 mol % to 10 mol % Li2O; 0.2 mol % to 14 mol % Na2O; 0 mol % to 1 mol % K2O; and 0 mol % to 4 mol % P2O5, Among them, Li2O (mol %) / R2O (mol %) is in the range of 0.337 to 0.4, R2O = Li2O + Na2O + K2O +Rb2O + Cs2O, and the sum of all components of the glass is 100 mol %.
4. A lithium aluminosilicate glass comprising: 55 mol % to 75 mol % SiO2; 10 mol % to 17 mol % Al2O3; 2.5 mol % to 7.5 mol % B2O3; 7 mol % to 10 mol % Li2O; 0.2 mol % to 14 mol % Na2O; 0 mol % to 1 mol % K2O; and 0 mol % to 4 mol % P2O5, Among them, Li2O (mol %) / R2O (mol %) is in the range of 0.20 to 0.4, R2O = Li2O + Na2O + K2O +Rb2O + Cs2O, and the sum of all components of the glass is 100 mol %.
5. The lithium aluminosilicate glass according to any one of claims 1 to 4, comprising 0.6 mol % to 4 mol % Na2O.
6. The lithium aluminosilicate glass according to any one of claims 1 to 4, wherein: The lithium aluminosilicate glass is ion-exchanged, and the ion-exchanged lithium aluminosilicate glass has a compressive layer extending from at least one surface into the glass to a layer depth of at least 70 μm, the compressive layer having a maximum compressive stress of at least 600 MPa.
7. The lithium aluminosilicate glass according to any one of claims 1 to 4, wherein: The lithium aluminosilicate glass has a Vickers crack initiation threshold of at least 10 kgf and a Knoop scratch threshold of at least 8 N.
8. A lithium aluminosilicate glass product, wherein: The lithium aluminosilicate glass article is formed from a glass comprising: 55 mol % to 75 mol % SiO2; 9 mol % to 18 mol % Al2O3; 2.5 mol % to 20 mol % B2O3; and 3 mol % to 20 mol % Li2O, wherein Li2O (mol %) / R2O (mol %) is in the range of 0.20 to 0.4, R2O = Li2O + Na2O + K2O + Rb2O + Cs2O, and the sum of all components of the glass is 100 mol %, and wherein the lithium aluminosilicate glass is ion exchanged and has a compressive layer extending from at least one surface into the glass article to a layer depth of at least 70 μm, the compressive layer having a maximum compressive stress of at least 600 MPa, wherein the glass article has a Vickers crack initiation threshold of at least 10 kgf and a Knoop scratch threshold of at least 8 N, and the sum of all components of the glass is 100 mol %.
9. A lithium aluminosilicate glass product, wherein: The lithium aluminosilicate glass article is formed from a glass comprising: 55 mol % to 75 mol % SiO2; 10 mol % to 18 mol % Al2O3; 7 mol % to 14 mol % Li2O, 0.2 mol % to 5 mol % Na2O; 0 mol % to 1 mol % K2O; 3 mol % to 7 mol % B2O3; and 0 mol % to 1 mol % P2O5, wherein the lithium aluminosilicate glass article is ion exchanged and has a compressive layer extending from at least one surface into the glass article to a layer depth of at least 70 μm, the compressive layer having a maximum compressive stress of at least 600 MPa, wherein the glass article has a Vickers crack initiation threshold of at least 10 kgf and a Knoop scratch threshold of at least 8 N, the sum of all components of the glass is 100 mol %, and wherein R2O-Al2O3 is -0.5 to 0, wherein R2O=Li2O+Na2O+K2O+Rb2O+Cs2O.
10. A consumer electronic product comprising: a housing having a front surface, a rear surface, and side surfaces; an electronic component at least partially located within the housing, the electronic component including at least a controller, a memory, and a display, the display being located at or adjacent to the front surface of the housing; as well as a cover glass disposed above the display, Wherein, at least one of a portion of the shell or the cover glass comprises the lithium aluminosilicate glass product as described in claim 8 or 9.
Citation Information
Patent Citations
Reinforced glass substrate
CN101522584A
Two-step method for strengthening glass
CN103068759A
Ion exchangeable glass with deep compressive layer and high damage threshold
CN103282318A
Ion exchanged glass with high resistance to sharp contact failure and articles made therefrom
US20130045375A1
Strengthening glass by multiple alkali ion exchange
US3433611A
